Functional complementarity and specialisation: The role of biodiversity in plant-pollinator interactions - Blüthgen, N.; Klein, A. M.
Ecological niche breadth (specialisation)and niche differentiation (complementarity)play a key role for species coexistence and hence biodiversity. Some niche dimensions of a species represent ecosystem functions or services such as pollination (functional niche). When species differ in their contribution to some collective function (functional complementarity), this implies that functions from several species are required for a high overall functional performance level. Applied to plant-pollinator interactions, functional complementary suggests that a higher diversity of pollinators contributes to an increased pollination success of the plants or, in turn, that a higher diversity of flowers may better sustain the consumers' requirements. Complementarity can affect functioning at different scales: the collective functioning of the target community, a single species, an individual or even a part of the individual, e.g. a single flower.